Distribution of blood groups in cats in Kyiv and Kyiv Oblast (Ukraine) - M. O. Malyuk; Y. Y. Dovbnia; V. V. Klymchuk; V. V. Honchar; N. І. Boiko; V. V. Solomon (Regulatory Mechanisms in Biosystems, 2024)
There are numerous cat breeds, grouped according to the phylogenetic or geographic origin. A plethora of reports have been published regarding the distribution and prevalence of the blood groups in pedigree and non-pedigree cats, but in Ukraine such data have not been systematically generalized. Therefore, the objectives of our research were to study the distribution of the blood groups in cats according to their breed features and enumerate the percentage proportion of each group in relation to the general number of the examined cats, and also identify the blood group of both the donor and recipient. In this study, we present the data on the blood groups and breeds of cats that we came across in 2018–2023. For each breed of cats, we estimated the percentage of prevalence in Kyiv and Kyiv Oblast. The general number of patients in our statistical studies was 519. Having analyzed the obtained results and having grouped the animals according to the blood groups, we see that the blood groups A and B were most often found in mixed-breed cats, accounting respectively for 55.4% (250 cases) and 33.3% (18 animals) of the general number. Also, we should note that according to our studies, the other commonest breeds of cats were the Scottish Folds, in which the group A was found in 7.8%, 35 cases, and the group B in 22.2% and 14.8%, in 12 and 8 animals, respectively. The AB blood group system is the most important cat system, and identifying the blood group using specific methods is an important step towards avoiding or reducing the risk of side-effects in the recipient patient during transfusion. Inferring from our study, the AB system was found only in 14 animals over a five year period, most commonly in Scottish Fold, measuring 50.0%, or 7 individuals.